Preparation method and application of electrolytic manganese residue catalyst
The catalyst is prepared by low-temperature anaerobic pyrolysis treatment and pickling, which solves the problems of high energy consumption and pollution in electrolytic manganese slag treatment, and realizes the resource utilization of electrolytic manganese slag and the efficient degradation of water pollutants.
Patent Information
- Application Number
- CN202411831552.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-18
AI Technical Summary
The prior art has problems such as high energy consumption, large carbon emissions, and metal ion leaching when treating electrolytic manganese slag, and conventional treatment methods cannot effectively degrade organic pollutants in water bodies.
The electrolytic manganese slag is treated with low-temperature anaerobic pyrolysis, and an electrolytic manganese slag catalyst is obtained by pickling. This catalyst can activate persulfate and efficiently degrade organic pollutants in the water.
The resource utilization of electrolytic manganese slag has been realized. The prepared catalyst has the COD removal ability of highly efficiently degrading antibiotic tetracycline and high COD antibiotic wastewater, and has good circulation stability, which is suitable for the field of sewage treatment.
Smart Images

Figure CN119838641A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sewage catalyst preparation, and specifically relates to a preparation method and application of an electrolytic manganese slag catalyst. Background Art
[0002] Manganese is widely used in industries such as steel, nonferrous alloys, battery materials, and chemicals, as well as in agriculture. Its main products include electrolytic manganese metal, electrolytic manganese dioxide, manganese-based ferroalloys, and manganese ore. Among them, electrolytic manganese slag is the acid leaching slag produced during the preparation of the electrolyte. It is a key pollutant in the electrolytic manganese industry. It mainly contains soluble manganese and chemical reagents such as ammonia water or ammonium sulfate added during the production of electrolytic manganese. The grade of manganese ore in my country is relatively low, so 8-10 tons of electrolytic manganese slag will be produced for every ton of metallic manganese produced. At present, the conventional treatment method for electrolytic manganese slag is stockpiling, but stockpiling will consume a large area of land, and since electrolytic manganese slag belongs to Class II general industrial solid waste, stockpiling may also cause safety problems and environmental pollution, such as inadequate anti-seepage, anti-leakage and anti-corrosion of manganese slag storage, which pollutes the surface and groundwater; during the construction and operation of manganese slag storage, the dam body is unstable, dam collapse or dam break occurs, causing safety accidents or polluting water bodies; the slag storage management is not standardized and irresponsible, resulting in disorderly stacking of electrolytic manganese slag and pollution of the surrounding environment. In addition, electrolytic manganese slag contains CaSO4, SiO2, Al2O3, Fe2O3, MnO, etc., and stockpiling will cause a lot of resource waste. Therefore, harmless treatment and resource utilization of electrolytic manganese slag have become hot issues for electrolytic manganese slag.
[0003] The harmless and resource-based treatment methods of electrolytic manganese slag include the preparation of unburned bricks, fertilizers, ceramic materials, adsorption materials, etc. However, there are more or less technical problems, as well as high costs and low resource utilization. Currently, preparing electrolytic manganese slag into valuable materials with catalytic properties has become a new high-value-added and effective way to reduce the hazards of manganese slag.
[0004] Shi Shajun et al. used sodium hydroxide to modify electrolytic manganese slag to prepare a modified electrolytic manganese slag, which can activate persulfate to degrade tetracycline hydrochloride in aqueous solution (Shi Shajun, Huang Ping. Modified electrolytic manganese slag activates persulfate to degrade tetracycline hydrochloride [J]. Water Purification Technology, 2023, 42(5): 102-108, 138.).
[0005] Chinese patent CN113634268A discloses a modified electrolytic manganese dioxide waste residue catalyst and its preparation method and application. The preparation method comprises the following steps: calcining the electrolytic manganese dioxide slag at 400-800°C for 1-2h and then impregnating the catalyst with an acid solution. The prepared modified electrolytic manganese dioxide waste residue catalyst can catalyze hydrogen peroxide or persulfate to rapidly and efficiently oxidize and remove antibiotics, fuels and flotation agents in mineral processing wastewater in a wide pH range, and has the advantages of low cost and simple preparation process.
[0006] However, the steps of alkaline modification are cumbersome and require the addition of raw materials such as EDTA, which is prone to secondary pollution; high-temperature calcination has high energy consumption and carbon emissions, and there is leaching of metal ions, so it also has great limitations. Therefore, it is necessary to develop a low-energy, green and simple process preparation method for electrolytic manganese slag catalyst to degrade organic pollutants in water. Summary of the invention
[0007] In view of the above technical problems, the present invention provides a preparation method and application of an electrolytic manganese slag catalyst. The electrolytic manganese slag is pyrolyzed and pickled at 200°C under anaerobic conditions to obtain an electrolytic manganese slag catalyst, which can be used as a catalyst for activating persulfate to efficiently degrade organic pollutants, effectively remove antibiotic tetracycline pollutants in water and remove COD from antibiotic wastewater.
[0008] In order to achieve the above object, the present invention provides a method for preparing an electrolytic manganese slag catalyst, comprising the following steps: (1) Pyrolysis of electrolytic manganese slag; (2) crushing and sieving to obtain electrolytic manganese slag powder; (3) Acid washing, water washing and precipitation to obtain an electrolytic manganese slag sample; (4) filtering and drying to obtain the electrolytic manganese slag catalyst; Preferably, the pyrolysis temperature is 100-200° C., the heating rate is 5-10° C. / min, and the insulation time is 1-2 h.
[0009] Preferably, the pyrolysis is carried out under anaerobic conditions.
[0010] Further preferably, the anaerobic condition is formed by introducing nitrogen or argon into the reaction container.
[0011] Preferably, the particle size of the electrolytic manganese slag powder in step (2) is 38-75 μm.
[0012] Preferably, the mass ratio of the acid in step (3) to the electrolytic manganese slag powder is 15-25:1.
[0013] Further preferably, the mass ratio of the acid in step (3) to the electrolytic manganese slag powder is 20:1.
[0014] More preferably, the acid is sulfuric acid with a concentration of 1-2 mol / L.
[0015] Preferably, the drying in step (4) is vacuum drying.
[0016] Further preferably, the vacuum degree of the vacuum drying is -0.08~-0.10MPa, the temperature is 50~70°C, and the time is 8~12h.
[0017] The invention also provides an application of an electrolytic manganese slag catalyst in degrading organic polluted wastewater.
[0018] Preferably, the pollutants in the organically polluted wastewater are antibiotics.
[0019] The beneficial effects of the present invention are: 1. The electrolytic manganese slag is pyrolyzed at 200°C by low-temperature oxygen-free pyrolysis treatment, and the electrolytic manganese slag catalyst is obtained by acid washing, so that the non-metallic sites on the surface of the waste electrolytic manganese slag are fully utilized, and a degradation agent capable of degrading organic pollutants in water is prepared. The preparation method is simple and efficient, and the raw materials are easily available, which is suitable for large-scale promotion and application to achieve the purpose of waste resource utilization.
[0020] 2. The catalyst prepared by the present invention can activate PDS to degrade tetracycline, an antibiotic pollutant in water, and the degradation rate of TC can reach 96.5% within 25 minutes. It can be widely used in the field of sewage treatment, and has a wide pH range and adaptability to different water matrices. The reaction pH has a good degradation effect within 3-9, so it can be promoted and applied to a certain extent.
[0021] 3. The catalyst prepared by the present invention has good cyclic stability. After 5 cycles, the degradation efficiency is still above 80%, and the metal Mn leaching rate is low (3.078 μg / L). It is applied to the treatment of high-COD antibiotic wastewater, and 57.50% of COD can be removed in 2.5 h, which has practical application prospects.
[0022] 4. The present invention adopts a pyrolysis method under low temperature and anaerobic conditions to prepare the electrolytic manganese slag catalyst. Compared with high temperature calcination, it is more conducive to the preservation of organic compounds in the electrolytic manganese slag, and the organic functional groups therein can better fix metallic manganese and reduce the leaching of metal ions; in addition, the low-temperature pyrolysis process will also cause the electrolytic manganese slag to form a relatively stable carbon skeleton structure (C6N2) and a large number of organic oxygen-containing functional groups and defect sites, including N-COO and C=O, which play a vital role in activating PDS. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 FT-IR spectra of EMR prepared at different temperatures in Example 5.
[0024] Figure 2 1 is the XPS spectra of EMR prepared at different temperatures in Example 5, wherein a is the C 1s spectrum, b is the O 1s spectrum, and c is the N 1s spectrum.
[0025] Figure 3 This is a diagram of the catalytic degradation of EMR prepared at different temperatures in Example 6.
[0026] Figure 4 The catalytic degradation of EMR2 at different pH values in Example 7 is shown in FIG. Figure 5 This is a diagram showing the catalytic degradation of EMR2 in different water matrices in Example 8.
[0027] Figure 6 The catalytic degradation of the electrolytic manganese slag catalyst and the dissolution of manganese ions at different cycle times in Example 9 are shown in FIG.
[0028] Figure 7 This is a diagram showing the catalytic degradation of the electrolytic manganese slag catalyst prepared under different atmospheres in Example 10.
[0029] Figure 8 This is a graph showing the adsorption-degradation experimental results in Example 11.
[0030] Fig. 9 This is a graph showing the degradation of COD by different catalysts in Example 12. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is further explained below in conjunction with the accompanying drawings and specific embodiments. It is worth noting that the following embodiments are only preferred embodiments of the present invention and should not be understood as limiting the present invention. The protection scope of the present invention shall be based on the contents recorded in the claims. Any modification or replacement made by those skilled in the art to the technical solution of the present invention without creative work shall fall within the protection scope of the present invention.
[0032] In the following examples, the electrolytic manganese slag is provided by Changyang Kairong Electrolytic Manganese Co., Ltd., and its material composition is as follows:
[0033] Example 1 (1) placing the electrolytic manganese slag in a tubular furnace, heating it to 200°C at a heating rate of 10°C / min under a nitrogen atmosphere, and then keeping it at that temperature for 1 hour to complete low-temperature oxygen-free pyrolysis; (2) crushing the electrolytic manganese slag after pyrolysis and sieving it through a 200-mesh sieve to obtain electrolytic manganese slag powder; (3) Mix the electrolytic manganese slag powder with 1 mol / L sulfuric acid solution (the mass ratio of sulfuric acid solution to electrolytic manganese slag powder is 1.5:1), stir for 2 h, filter and retain the precipitate, and then wash the precipitate with water 3 times to obtain an electrolytic manganese slag sample; (4) The electrolytic manganese slag sample was filtered, and then the solid matter was dried in a vacuum drying oven at -0.08 MPa and 60°C for 12 h to obtain an electrolytic manganese slag catalyst, which was recorded as EMR2.
[0034] Example 2 The method and steps are the same as those in Example 1, except that the heating rate in step (1) is changed to 8° C. / min to prepare an electrolytic manganese slag catalyst.
[0035] Example 3 The method and steps are the same as those in Example 1, except that the heating rate in step (1) is changed to 5°C / min to prepare an electrolytic manganese slag catalyst.
[0036] Example 4 The method and steps are the same as those in Example 1, except that the nitrogen atmosphere in step (1) is replaced by an argon atmosphere to prepare an electrolytic manganese slag catalyst, which is denoted as Ar-EMR2.
[0037] Comparative Example 1 The electrolytic manganese slag was crushed, passed through a 200-mesh sieve, and then vacuum dried to obtain an electrolytic manganese slag catalyst, wherein the vacuum drying conditions were the same as those in Example 1, and were recorded as EMR.
[0038] Comparative Example 2 The method and steps are the same as those in Example 1, except that the pyrolysis temperature in step (1) is changed to 100° C. to prepare an electrolytic manganese slag catalyst, which is denoted as EMR1.
[0039] Comparative Example 3 The method and steps are the same as those in Example 1, except that the pyrolysis temperature in step (1) is changed to 300° C. to prepare an electrolytic manganese slag catalyst, which is denoted as EMR3.
[0040] Comparative Example 4 The method and steps are the same as those in Example 1, except that the pyrolysis temperature in step (1) is changed to 400° C. to prepare an electrolytic manganese slag catalyst, which is denoted as EMR4.
[0041] Comparative Example 5 The method and steps are the same as those in Example 1, except that the pyrolysis temperature in step (1) is changed to 600° C. to prepare an electrolytic manganese slag catalyst, which is denoted as EMR6.
[0042] Comparative Example 6 The method and steps are the same as those in Example 1, except that the nitrogen atmosphere in step (1) is replaced by an air atmosphere to prepare an electrolytic manganese slag catalyst, which is denoted as Air-EMR2.
[0043] Comparative Example 7 The method and steps are the same as those in Example 1, except that step (3) is omitted, to prepare an electrolytic manganese slag catalyst.
[0044] Example 5 The electrolytic manganese slag catalysts prepared in Example 1 and Comparative Examples 1-5 were subjected to Fourier infrared spectroscopy (FT-IR spectrum) and X-ray photoelectron spectroscopy (XPS spectrum). The results are shown in the figure: All samples have stretching vibration peaks of CH, CO and C=C / C=O, indicating that the manganese slag has a relatively stable carbon skeleton structure; in addition to these peaks, EMR1 and EMR2 prepared at low temperature also have a peak at 1426 cm −1 and 1150 cm -1 A new peak N-COO ( ) and CN; At the same time, as the pyrolysis temperature gradually increases, the N-COO peak disappears ( Figure 1 ), indicating that heat treatment, especially at low temperature, is conducive to the construction of N-COO and CN groups. Low-temperature anaerobic pyrolysis increases the defect content by producing electron-rich groups (CN / C=O), thereby producing more active sites to activate PDS. Studies have shown that electron-rich groups such as C=O groups on the surface of carbon materials can promote the generation of persistent free radicals (PFRs) and can also produce singlet oxygen ( 1 O2), free radicals (PFR) H and singlet oxygen ( 1 The increase of O2 content can activate PDS and degrade organic pollutants in water.
[0045] Figure 2 The electron binding energy peaks of C 1s in a at 284.6 eV, 285.3 eV, 286.4 eV and 288.6 eV are assigned to CC / C=C, CN, CO and C=O, respectively. The C 1s spectrum after heat treatment shows that CN is newly formed on EMR2, and the relative content of C=O also increases (11.36%→13.47%). The peaks of O 1s XPS spectrum at 531.2 eV, 532.3 eV and 533.4 eV are assigned to CO, C=O and OC=O, respectively. Figure 2 b). After heat treatment, the peak areas of C=O and OC=O increased significantly compared with those before modification. The N configuration in the high-resolution spectrum of N 1s is composed of pyridinic N (398.3 eV), pyrrolic N (399.5 eV), and graphitic N (401.8 eV) ( Figure 2 c). After heat treatment, the pyridinic N content decreased (11.86%→9.74%), and the pyrrolic N content increased from 54.13% to 76.46%, indicating that low-temperature heat treatment enhanced the conversion of pyridinic N to pyrrolic N. Low-temperature heat treatment resulted in the formation of CN, C=O and pyrrolic N on EMR2. These groups easily formed positively charged centers with adjacent carbon atoms, adsorbed nucleophilic PDS and participated in activation, thereby promoting the degradation of TC. The results were consistent with the FT-IR spectrum ( Figure 1 ) are consistent.
[0046] Example 6 The electrolytic manganese slag catalysts prepared in the above Example 1 and Comparative Examples 1-7 were used to carry out antibiotic degradation experiments, and the specific steps are as follows: (1) Adding electrolytic manganese slag catalyst to a 10 mg / L tetracycline solution and mixing until adsorption-desorption equilibrium is reached; wherein the mass ratio of the tetracycline solution to the electrolytic manganese slag catalyst is 4:1; (2) Potassium persulfate was added, and the supernatant was taken at a certain reaction time interval and the concentration change of tetracycline was detected by high performance liquid chromatography, where the detection wavelength was λ max =360nm, the mass ratio of potassium persulfate to electrolytic manganese slag catalyst is 1:1.
[0047] The results showed that the samples EMR1, EMR2 and EMR3 treated at low temperature all had good degradation ability for tetracycline, among which EMR2 had the best catalytic activity, with a degradation efficiency of 96% within 25 min, which was 1.74 times that of EMR (degradation efficiency was 55%). Figure 3 ), indicating that PDS activated by EMR2 can achieve efficient degradation of tetracycline. As the pyrolysis temperature further increases, the degradation efficiency of tetracycline gradually decreases, indicating that the pyrolysis temperature can directly affect the degradation efficiency of EMR, and with the change of pyrolysis temperature, the degradation efficiency shows a trend of first increasing and then decreasing.
[0048] Example 7 The method and steps are the same as those in Example 5, except that the initial pH of the tetracycline solution is adjusted to 2.86, 4.97, 6.36, 9.14, and 11.06, respectively, and the change in tetracycline concentration is detected, wherein the electrolytic manganese slag catalyst is the one prepared in Example 1.
[0049] The results are as follows Figure 4 As shown in the figure, when the pH value is between 3 and 9, EMR2 activated PDS can effectively degrade TC, and acidic and neutral conditions have a positive effect on the degradation of TC. This is because in the pH range of 3.3 to 7.7, TC is mainly in the form of cationic TCH3 + and TCH20, and with the increase of pH, TCH3 + Gradually converted to TCH20, therefore, the electronic attraction between TC and PDS is stronger. The results show that EMR2 can activate PDS to degrade TC in a wide pH range.
[0050] Example 8 The method and steps are the same as those in Example 5, except that the water matrix of the tetracycline solution is changed to ultrapure water, tap water, secondary effluent and lake water, tetracycline is added to make its initial concentration 10 mg / L, and the change of tetracycline concentration is detected.
[0051] The results are as follows Figure 5 As shown: Compared with pure water (degradation rate 98%), the degradation efficiency of TC in the other three water matrices only slightly decreased to 95%, 90% and 92%, indicating that the EMR2 / PDS system has good adaptability to actual water quality and therefore has a wide range of applications.
[0052] Example 9 Cycle Experiment (1) Adding the electrolytic manganese slag catalyst prepared in Example 1 to a 10 mg / L tetracycline solution, and mixing until adsorption-desorption equilibrium is reached; wherein the mass ratio of the tetracycline solution to the electrolytic manganese slag catalyst is 4:1; (2) Potassium persulfate was added, and the change in tetracycline concentration was detected after 25 minutes, wherein the mass ratio of potassium persulfate to electrolytic manganese slag catalyst was 1:1.
[0053] (3) After the degradation is completed, the electrolytic manganese slag catalyst is collected, washed three times with 2 mol / L HCl solution, then washed with up water until the filtrate is neutral, and dried in an oven at 60°C; (4) The dried electrolytic manganese slag catalyst was added into the tetracycline solution again to conduct a degradation experiment. This was repeated 5 times and the degradation of tetracycline was recorded each time.
[0054] The results are as follows Figure 6 As shown: after five cycles, the degradation rate of TC by the system only decreased by 17%, but still reached 80%, indicating that EMR2 / PDS / TC has good cycle stability. In addition, the Mn content in the filtrate after multiple cycles was determined and it was found that the Mn leaching concentration in the first cycle was the highest, 0.067 mg / L, but it was also lower than the first-level emission standard of total manganese (2.0 mg / L) specified in the comprehensive sewage discharge standard. The Mn content in the filtrate after the second cycle was greatly reduced (0.05 mg / L), and after five cycles, almost no Mn was dissolved, and its content was only 0.003 mg / L, indicating that the EMR2 / PDS system has good cycle stability.
[0055] Example 10 (1) The electrolytic manganese slag catalysts prepared in Examples 1, 4 and Comparative Example 6 were added to a tetracycline solution having a concentration of 10 mg / L and mixed until adsorption-desorption equilibrium was reached; wherein the mass ratio of the tetracycline solution to the electrolytic manganese slag catalyst was 4:1; (2) Potassium persulfate was added, and the supernatant was taken at a certain reaction time interval and the concentration change of tetracycline was detected by high performance liquid chromatography, where the detection wavelength was λ max =360nm, the mass ratio of potassium persulfate to electrolytic manganese slag catalyst is 1:1.
[0056] The results show that the EMR samples obtained by pyrolysis under two inert atmospheres can completely degrade TC within 25 min, while the degradation rate of the EMR prepared in comparative example 6 under air atmosphere decreases by about 3 times ( Figure 7 ), indicating that EMR can activate PDS and efficiently degrade TC through low-temperature anaerobic pyrolysis.
[0057] Example 11 Adsorption-degradation experiment (1) Dark reaction adsorption: Take the EMR2 prepared in Example 1 and add it to the tetracycline solution. Adsorb it in the dark for 1 hour, and then calculate the change of tetracycline concentration before and after the addition of EMR2. (2) Degradation: Experimental group (EMR2 / PDS): EMR2 and an equal amount of potassium persulfate as that of EMR2 were added to the tetracycline solution; Control group 1 (EMR2): EMR2 was added to the tetracycline solution; Control group 2 (PDS): potassium persulfate was added to the tetracycline solution; Control group 3 (EMR1 / PDS): EMR1 and an equal amount of potassium persulfate as EMR1 were added to the tetracycline solution. After 25 min, the concentration of tetracycline was detected and the reaction rate was calculated.
[0058] The results are as follows Figure 8 As shown in the figure, 38% of tetracycline was adsorbed on EMR2 in the dark reaction adsorption experiment, indicating that EMR2 has good adsorption properties and can help the catalytic degradation of tetracycline. When only potassium persulfate was used in control group 2, the degradation rate of tetracycline was only 17%, and when only EMR2 was used in control group 1, the degradation rate was only 7%. When EMR2 and potassium persulfate were used at the same time, the degradation rate could be as high as 96%, and the reaction rate was 0.103 min -1 , 21 times that of PDS and EMR2 alone (0.005 min -1 ) and 34 (0.003 min -1 ) times.
[0059] Example 12COD removal experiment (1) Take tetracycline solution and adjust the pH value to 3, 5, 7, and 9 respectively, where the concentration of tetracycline in the tetracycline solution is 10 mg / L and the initial COD is 592.64 mg / L; (2) adding the electrolytic manganese slag catalyst EMR2 prepared in Example 1 to the tetracycline solution and mixing until adsorption-desorption equilibrium is reached; wherein the mass ratio of the tetracycline solution to the electrolytic manganese slag catalyst is 4:1; (3) adding potassium persulfate, taking the supernatant at a certain reaction time interval to detect the change in COD concentration, and the mass ratio of potassium persulfate to electrolytic manganese slag catalyst is 1:1; (4) Repeat steps (1) to (3), except that EMR2 (prepared in Example 1) is replaced by EMR (prepared in Comparative Example 1); The results are as follows Fig. 9 As shown in the figure, under the same experimental conditions, the COD of EMR2 catalyst dropped to 251.872 mg / L (removal rate 57.50%) within 2.5 h, which was higher than that of EMR (340.768 mg / L, removal rate 42.50%), indicating that EMR2 prepared by low-temperature anaerobic pyrolysis has a greater potential for degrading actual wastewater.
Claims
1. A method for preparing an electrolytic manganese slag catalyst, characterized in that: The steps include: (1) Pyrolysis of electrolytic manganese slag; (2) crushing and sieving to obtain electrolytic manganese slag powder; (3) Acid washing, water washing and precipitation to obtain an electrolytic manganese slag sample; (4) Filter and dry to obtain the electrolytic manganese slag catalyst.
2. The preparation method according to claim 1, characterized in that: The pyrolysis temperature is 100-200° C., the heating rate is 5-10° C. / min, and the time is 1-2 h.
3. The preparation method according to claim 1, characterized in that: The pyrolysis is carried out under oxygen-free conditions.
4. The preparation method according to claim 1, characterized in that: The particle size of the electrolytic manganese slag powder in step (2) is 38-75 μm.
5. The preparation method according to claim 1, characterized in that: The mass ratio of the acid to the electrolytic manganese slag powder in step (3) is 15-25:
1.
6. The preparation method according to claim 5, characterized in that: The acid is sulfuric acid with a concentration of 1-2 mol / L.
7. The preparation method according to claim 1, characterized in that: The drying in step (4) is vacuum drying.
8. The preparation method according to claim 7, characterized in that: The vacuum degree of the vacuum drying is -0.08~-0.10MPa, the temperature is 50~70°C, and the time is 8~12h.
9. Use of the electrolytic manganese slag catalyst prepared by the preparation method according to any one of claims 1 to 8 in degrading organic polluted wastewater.
10. The use according to claim 9, characterized in that: The pollutants in the organic polluted wastewater are antibiotics.
Citation Information
Patent Citations
Modified electrolytic manganese dioxide waste residue catalyst as well as preparation method and application thereof
CN113634268A
Cited By
Electrolytic manganese residue catalyst for activating persulfate salt, preparation method and application thereof
CN122538158A